Maize and Weed Growth under Multispecies Competition. Issue 3 (1st May 2015) - Yousefi, Ali Reza; Karimmojeni, Hassan; Mashhadi, Hamid Rahimian; Amini, Rouhollah
ABSTRACT: Multispecies competition effects of Xanthium strumarium L. and Datura stramonium L. have not been characterized in maize ( Zea mays L.). Such information would be useful in developing an integrated approach to managing these two problematic weeds. Field experiments were conducted during 2 yr to evaluate multiple weed species interference of X. strumarium and D. stramonium at the total densities of 0, 4, 8, 12, and 16 plants m −2 (alone, and all possible combinations of the two weeds) with maize. Crop yield was associated with the density of D. stramonium and X. strumarium and decreased severely with increasing weed density. The maximum maize yield loss (63%) occurred when 12 X. strumarium and 4 D. Stramonium plants m −2 were allowed to compete with the crop. The total weed density (expressed in X. strumarium equivalent density) required to cause a 5% maize yield loss was about 0.50 and 0.56 plants m −2 in 2006 and 2007, respectively. Total canopy leaf area index and crop yield were reduced more strongly by competition with X. strumarium than with D. stramonium . Averaged over multispecies populations, X. strumarium contributed 84 and 67% of the total weed biomass in the first and second years, respectively. Owing to the high competitive ability and biomass production of X. strumarium in mixed crop and weed communities, it should be given a greater priority for control than D. stramonium in maize.